Developed and Field Performance Evaluation of a Combined Cultivator - Mohamed Hassan Dahab; Abdalla N. O. Kheiry; Mohamed Hamid Numan (Journal of Agronomy Research, 2021)
Sugar cane production requires a number of operations to be carried out in the field through number of implements and machines. Therefore, time consuming and required large amount of energy. A combined field cultivator was designed in Kenana agricultural implements factory (KAIF) to carry out at one time multi operations (cultivation, furrow-reforming and Fertilizer placement). This is to increase field productivity, reduce farm power and lower operation time and cost. The combined implement was evaluated in Kenana cultivation fields and compared with three individual implements, rigid tine cultivator, furrow-reformer and fertilizer applicator. The measured parameters were drawbar pull, power requirements, field capacity, fuel consumption and total time in the field. The results showed highly significant differences at 1% level between the different implements for the field capacity, fuel consumption and significant differences at 5% for the drawbar pull. A power requirement in (kW) for the combined cultivator was 77% of those individual implements. Total time per feddan to accomplish the required operations by the combined cultivator was 57% of that required by the individual implements. Fuel consumption was reduced to 57% when combined implement was used compared to that consumed by individual implements. It was concluded that the combined cultivator was effective in increasing field productivity and reducing power and cost of operation.
Keywords: Sugar cane